“control químico de tagosodes orizicolus (muir) en el cultivo de arroz (oryza sativa), variedad capirona en el bajo mayo” - Flores Rios, Claudia Isabel (2002)
The present Research Thesis named "Chemical control of Tagosodes orizico/us (Muir) on rice crop (Oryza Zativa), capirona variety, on Cacatachi District", was developed on the second campaign of 1999 in the field belonging to the National University of San Martín, Cacatachi District, Province of San Martin (Bajo Mayo Valley). The place is distinguished by a humid tropical climate with annual average precipitations of 1 1 OOmm, temperatures fluctuating between annual maximum 37 ºC and minimum 22 ºC and with an annual relative humidity of 65 % at 350 msl. and clay soils. The aim of the present work was to evaluate the control of T. orizicolus using 4 pesticides (lmidaclprid, Fenthion, Cipermetrina and Monocrotofos) on different concentrations and the effect of the application on the beneficia! fauna, with emphasis on predators. 8 treatments were applied with 4 repetitions with a complete block design at random. Evaluations on initial populations of T. orizicolus were made one day before application, finding 46 females and 51 males on average of 1 O double PASES. Treatments used were:, lmidacloprid 80 ce/Ha, lmidacloprid 100 ce /Ha, Gipermetrina 250 ce/Ha, Cipermetrina 500 ce/Ha Fenthion 750 ce/Ha, Monocrotofos 750 ce/Ha, Cipermetrina 250 ce/Ha + Monocrotofos 750 ce/Ha and the witness. The application was made 1 O days after transplant, making periodical evaluations each 4 days up to 20 days after application and then each 7 days up to 41 daa. For every treatment, it was observed that adult population, female and male, decreases constantly up to the 27th daa. Reaching for females averages between 0.5 (lmidacloprid 80 and 100 ce/Ha) and 8,5 (witness) and reaching for males averages between 1 (lmidacloprid 1 OOcc/Ha) and 5,75 individuals (Fenthion 750 ce/Ha). On the 34 th daa the highest averages of population were reached, outstanding the treatments with Fenthion 750 ce/Ha with 54 and 42,5 individuals for females and males respectively. The lowest population averages in this period were reached by lmidacloprid 80 ce/Ha with 4, 75 individuals in females and lmidacloprid 100 ce/Ha treatrnent with 3,5 male individuals. We assume that the initial population detected on crop, is due to migrations, because of the absence of nymphs during the first 12 days after the application. Later a population explosion occurs at 20 daa. This suggests that T. orizicolus cycle for the place conditions where the research was carried out, fluctuates around 30 days approximately. The predator population fluctuates on averages between 0.5 and 4 , during all evaluations. Comparing with initial evaluations of 8 individuals, we conclude that the pesticides used caused a mortality between 60 and 100%.